Improving access to surgery in low- and middle-income countries through improved emergency and essential surgical care provision at district hospitals - Westwood, Jessica (Division of General Surgery, 2026)
Surgical conditions contribute to one-third of the global burden of disease, yet many individuals in low- and middle-income countries (LMICs) lack access to emergency and essential surgical care. In South Africa, 86% of the population resides within 2-hours of a district hospital equipped with basic surgical capabilities. Improving access to emergency and essential surgical care at these district hospitals could reduce morbidity and mortality related to surgical conditions. However, detailed knowledge of the surgical capacity at district hospitals is limited. Madwaleni District Hospital is a 180-bed rural hospital in the Eastern Cape province of South Africa. Surgery at the facility is provided by a diverse team of doctors, ranging from community service medical officers to family medicine specialists. This study aims to describe the volume and breadth of emergency and essential surgical services provided at Madwaleni Hospital in order to inform and enable future improvements in the surgical system. Methods: A retrospective audit of the district hospital surgical service was conducted. Data were extracted from the theatre register between January 2016 and December 2022. Data included patient demographics, surgical procedures, and surgical providers. A quantitative descriptive analysis was performed. Results: A total of 2616 surgical procedures were performed over the 7-year study period. The average monthly theatre volume grew from 27 procedures per month in 2016 to 41 procedures per month in 2022. Theatre utilisation averaged one theatre case per day over the study period. Caesarean sections predominated, accounting for 82% of all surgical cases. An expanding basket of care was observed, with 13 unique procedures performed in the first year and 12 unique procedures added during the next six years. These included obstetric, gynaecological, orthopaedic, urological and general surgical procedures. Family medicine registrars and family physicians performed the most procedures per person. Conclusion: District hospitals offer a vital opportunity to close the gap between the met and unmet need for surgery in LMICs. However, quality data describing emergency and essential surgical care at district hospitals in South Africa is scarce. This study demonstrates the capacity and opportunity to expand surgical services at rural district hospitals.